Development of an experimental set up for the detection of simulated partial discharges using acoustic emission system - Iynggaran M.Seva Bala Sundaram (2023)
This project report comprises of my study on creating an experimental setup to simulate the creation of partial Discharge. Partial Discharge test detection method which was studied in this project was the Acoustic Emission method. In line with this requirement, I have done literature survey regarding Partial Discharge phenomena. This includes a background study of when, where and how it occurs. The scope of this project has been simulation of Partial Discharge in a transformer. Thus the final product as the deliverable of the project is the discharge circuit.